Far from the equilibrium crystallization of oxide quantum dots in dried inorganic gels. (31st May 2018) - Costille, B; Dumoulin, M; Ntsame Abagha, A M; Thune, E; Guinebretière, R
Abstract: We synthesized, through the sol-gel process, far from the equilibrium amorphous materials in which heterogeneous crystallization allowed the formation of oxide quantum dots. The isothermal evolutions of the mean size of the nanocrystals and the crystallinity of the materials were determined through x-ray diffraction experiments. The heterogeneous crystallization is characterized by a kinetic behavior that is far from that expected, according to the classical nucleation theory. We demonstrate that the evolution of the crystallinity is characterized by an Avrami exponent largely smaller than 1. Finally, nanocrystals exhibiting a size significantly below their Bohr radius are obtained and the number of these nanocrystals increases during isothermal treatment, whereas their mean size remains quasi-constant.